Successful Management of a Severe Case of Bisphosphonates Related Osteonecrosis of the Jaw in a Multiple Myeloma Patient - Luchetti, César Gabriel (2009)
BRONJ is a serious oral complication of bisphosphonate treatment involving the exposure of necrotic maxillary or mandibular bone, occurring in 1.8 to 12.8 % of the cases with intravenous bisphosphonates administration, and is associated with pain, paresthesia and oral dysfunction generating an impairment of the quality of life. Treatment of this complication remains difficult and still the most useful action is prevention.